The SAGE handbook of developmental psychology and early childhood education - Whitebread, David, 1948-; Grau, Valeska; Kumpulainen, Kristiina, 1966-; McClelland, Megan; Perry, Nancy, 1946-; Pino-Pasternak, Deborah (SAGE Reference, 2019)
The SAGE Handbook of Developmental Psychology and Early Childhood Education explores a range of issues in early childhood development and education. With the expertise of a body of international contributors, the chapters provide a much-needed overview of current and future direction for the field. Employing a broad and comprehensive focus, the Handbook combines research and practice to investigate emotional and social development, well-being and mental health, language, cultural environments, as well as the role of parents in a child's development. Through the structure of the book, readers are guided through a wide range of educational and developmental discourses, arranged across the following thematic parts: Part One: Emotional Development; Part Two: Social Development; Part Three: Play, Development and Learning; Part Four: Memory and Understanding; Part Five: Learning, Language and Literacy; Part Six: Executive Functions, Metacognition and Self-Regulation. The book concludes with an examination of the key aspects of early development which need to be the focus of high quality early childhood education.- Resumé vydavatel
Keywords: vývojová psychologie; dětství; výchova a vzdělávání; developmental psychology; childhood; education; elektronické knihy; příručky; electronic books; handbooks and manuals